Transformasi Kurikulum Pendidikan Islam Melalui Keterampilan untuk Menanggulangi Darurat Keterampilan - Tiara Nurul Annisa'; Misbahul Arifin; Arini Nuora Darina; Ainul Yakin; Ahmad Faidul Mannan (Educational Research Center, 2025)
This study focuses on the efforts to transform the Islamic education curriculum at SMK Syarifuddin Lumajang through the integration of life skills and entrepreneurship as a strategy to address the future skills emergency. Using a qualitative method with a case study approach, this research explores the practice of curriculum reconstruction based on Islamic values relevant to 21st-century demands, through observations, in-depth interviews with teachers and students, and analysis of learning documents. The findings indicate that contextual and transformative Islamic education successfully integrates the strengthening of digital literacy, problem-solving, collaboration, and entrepreneurship practices based on halal products and digital marketing. This approach not only reinforces students’ religious character but also equips them with competitiveness, creativity, and readiness to face social and technological changes. The implications of this study encourage the development of an Islamic education curriculum that is more responsive, adaptive, and directly connected to the business world and the needs of modern society.